2015
DOI: 10.1177/1756283x15593693
|View full text |Cite
|
Sign up to set email alerts
|

Management of inflammatory bowel disease with oral serum-derived bovine immunoglobulin

Abstract: These results suggest that SBI improves clinical management of IBD patients who are not fully managed on traditional therapies. SBI should be considered for the nutritional support of IBD regardless of disease activity, location, phenotype, duration, or complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…Indeed, a number of clinical reports have described the effectiveness of SBI for managing the chronic loose and frequent stools found in these conditions. 18,19,21,30 Our results also showed an improvement in stool consistency leading to a reduction in the number of daily unformed stools in HIV-infected participants after 1 week of SBI treatment. Study participants also reported significant improvements in several other GI symptoms.…”
Section: Efficacy -Symptom Diary Scoressupporting
confidence: 61%
“…Indeed, a number of clinical reports have described the effectiveness of SBI for managing the chronic loose and frequent stools found in these conditions. 18,19,21,30 Our results also showed an improvement in stool consistency leading to a reduction in the number of daily unformed stools in HIV-infected participants after 1 week of SBI treatment. Study participants also reported significant improvements in several other GI symptoms.…”
Section: Efficacy -Symptom Diary Scoressupporting
confidence: 61%
“…Other adult IBD studies support similar results [5, 6]. A recent case report of a 13-year-old pediatric UC patient has also been presented, demonstrating clinical and inflammatory remission based on complete disappearance of symptoms within 4 weeks and decreased fecal calprotectin from >1,700 to <15 μg/g after 3 months of SBI use when added to other standard treatments [7].…”
Section: Introductionsupporting
confidence: 61%
“…Hence, further understanding of the clinical benefits with SBI therapy is required, while exploring the putative mechanisms of action of SBI, the goal of this study. In patients with IBS‐D following recurrent C.difficile infection, SBI restored normal bowel function in two patients treated in open‐label fashion (Crawford and Panas, ), suggesting potential effects on barrier function, mucosal immune function or, conceivably, the microbiome, but clearly requiring more rigorous study. In a single‐center, retrospective chart review of 45 patients with inflammatory bowel disease (38 Crohn's disease and 7 ulcerative colitis)) with limited to no response to traditional pharmaceutical therapies, the medical food, SBI, has been shown to improve symptom scores and clinical management (Shafran et al. ). SBI has been shown to bind and neutralize microbial components (Tomita et al. ; Navarro et al.…”
Section: Introductionmentioning
confidence: 99%